CONFIRMATORY FACTOR ANALYSIS (CFA): ANALISIS INSTRUMEN LINGKUNGAN PENDIDIKAN ISLAM DAN EFIKASI DIRI MAHASISWA: Confirmatory Factor Analysis (CFA): Instrument Analysis Of Islamic Educational Environment and Student’s Self-Efficacy - Ahmad Sayyidiman Hamidalloh; Ayu Utami (TA'LIMUNA: Jurnal Pendidikan Islam, 2026)
This study aims to test the validity and reliability of the Islamic Education Environment and Student Self-Efficacy instruments using the Confirmatory Factor Analysis (CFA) approach. The study employed a quantitative survey method involving 192 STAI Ma’had Aly Al-Hikam Malang students selected purposively. CFA analysis showed that the Islamic Education Environment construct had a good model fit with a CFI value of 0.904, RMSEA 0.088, and SRMR 0.066, and all indicators were significant with factor loadings ranging from 0.538 to 0.806. In contrast, the Self-Efficacy construct showed a less than ideal model fit (CFI = 0.814; RMSEA = 0.118), with two indicators not significant, suggesting they should be eliminated in the next model. This results affirm that a conducive Islamic educational environment is an important external factor in shaping students' self-confidence, while self-efficacy as an internal factor is more complex and requires refinement of its measurement structure. This study recommends strengthening self-efficacy through simultaneous interventions in the family environment, campus institutions, and the community. Penelitian ini bertujuan untuk menguji validitas dan reliabilitas instrumen Lingkungan Pendidikan Islam dan Efikasi Diri Siswa menggunakan pendekatan Analisis Faktor Konfirmatori (CFA). Penelitian ini menggunakan metode survei kuantitatif yang melibatkan 192 mahasiswa STAI Ma’had Aly Al-Hikam Malang yang dipilih secara purposif. Analisis CFA menunjukkan bahwa konstruk Lingkungan Pendidikan Islam memiliki model fit yang baik dengan nilai CFI 0,904, RMSEA 0,088, dan SRMR 0,066, dan semua indikator signifikan dengan muatan faktor berkisar antara 0,538 hingga 0,806. Sebaliknya, konstruk Efikasi Diri menunjukkan model fit yang kurang ideal (CFI = 0,814; RMSEA = 0,118), dengan dua indikator tidak signifikan, menunjukkan bahwa indikator tersebut harus dieliminasi pada model selanjutnya. Hasil ini menegaskan bahwa lingkungan pendidikan Islam yang kondusif merupakan faktor eksternal penting dalam membentuk kepercayaan diri siswa, sedangkan efikasi diri sebagai faktor internal lebih kompleks dan memerlukan penyempurnaan struktur pengukurannya. Studi ini merekomendasikan penguatan efikasi diri melalui intervensi simultan di lingkungan keluarga, lembaga kampus, dan masyarakat. Kata Kunci : Confirmatory Factor Analysis (CFA); Efikasi Diri; Lingkungan Pendidikan Islam.